PRIORITY PROBLEMS RELATED TO TAILING DUMPS OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
In the article for the first time are given aggregated data of all metal deposits tailing dumps of RA, are examined issues of their classification by hazard category, as well as other important unresolved problems related to tailings and are pointed the ways of their solution.
Keywords: mineral and raw material; technogenic formations; enrichment tails; hazard categories; utilization of waste; laws